Epidemiology of Botrytis cinerea on Grape: Wound Infection by Dry, Airborne Conidia - Coertze, S.; Holz, G. (South African Journal of Enology and Viticulture, 2017)
This study describes the infection of fresh wounds on berries exposed to freshly deposited airborne Botrytis cinerea conidia, and on berries carrying previously deposited conidia and germlings (latent infections). Grapes at bunch closure and at the mature (harvest) stage, as well as mature, cold-stored grapes, were used. The grapes were dusted with dry conidia in a settling tower. The inocula were subjected to conditions commonly encountered by the pathogen in grape bunches: dry conidia on dry berries under dry conditions, dry conidia on dry berries under high relative humidity, and dry conidia exposed to a film of water on the berry surface.  The mean number of wounds that yielded B. cinerea decay 14 days after inoculation was calculated. Fluorescence microscopy revealed that conidia occurred evenly as single cells on the grape berry surface and seldom landed at the wound periphery. They remained dormant on dry berries, but germinated freely on the unbroken skin and at the wound periphery on moist and wet berries. In the case of berries inoculated at bunch closure and harvest stages, wounds were not infected by conidia deposited on berries four days prior to wounding. This finding indicated that, following adhesion and the first stages of growth, the pathogen did not survive for extended periods on surfaces of immature and mature grape berries.  Freshly deposited dry conidia were needed to infect the wounds. The freshly deposited conidia furthermore needed free water, and not high humidity or wound exudates, to infect the fresh wounds. Proportions of wounds infected were extremely low. According to these findings, this mode of infection should not contribute to a gradual build-up of secondary inoculum and to B. cinerea epiphytotics in the vineyard. The previously and freshly deposited conidia both infected wounds made on cold-stored mature berries. Of the two inocula, freshly deposited conidia were more successful in causing wound infection. Therefore, in the event of wounding, postharvest decay would be caused primarily by conidia occurring on the grape berry surface, and not by mycelia in the berry skin.